2019
DOI: 10.1186/s13041-019-0436-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression meta-analysis of Parkinson’s disease and its relationship with Alzheimer’s disease

Abstract: Parkinson’s disease (PD) and Alzheimer’s disease (AD) are the most common neurodegenerative diseases and have been suggested to share common pathological and physiological links. Understanding the cross-talk between them could reveal potentials for the development of new strategies for early diagnosis and therapeutic intervention thus improving the quality of life of those affected. Here we have conducted a novel meta-analysis to identify differentially expressed genes (DEGs) in PD microarray datasets comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 47 publications
(65 reference statements)
3
57
2
Order By: Relevance
“…This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in blood transcriptomics of PD [38][39][40] . This could be confirmed for ATXN3 in the substantia nigra of PD patients 42 . Therefore, these genes have the potential to serve as blood biomarkers for PD vulnerability.…”
Section: Discussionsupporting
confidence: 52%
“…This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in blood transcriptomics of PD [38][39][40] . This could be confirmed for ATXN3 in the substantia nigra of PD patients 42 . Therefore, these genes have the potential to serve as blood biomarkers for PD vulnerability.…”
Section: Discussionsupporting
confidence: 52%
“…In a fourth relevance assessment step, to test the relevance of the mouse model to study molecular events leading to an early-PD like phenotype, the human orthologues of the lists of DEGs between genotypes (HET versus WT) obtained from the mouse data for each age (3M, 9M, 13M) were compared to the list of DEGs from a recent meta-analysis of transcriptomics data from post-mortem brain samples of PD patients and controls conducted by Kelly et al [48]. Thus, with these 4 relevance assessment steps, we evaluated whether the mouse model data can provide an adequate reflection of the alterations associated with early PD progression.…”
Section: Comparability Of the Mouse Model To Human Datamentioning
confidence: 99%
“…When comparing the DEGs obtained in this study to the list of DEGs from a meta-analysis of transcriptomics data from post-mortem brain samples from the SN midbrain region from a previous study [48], we observed a significant overlap with the DEGs between genotypes (HET versus WT) for 3 months old mice (45 genes, Fisher's exact test p-value = 0.003, see Table S7), but no overlap with the 5 DEGs obtained for 9 months old mice.…”
Section: Comparability Of the Mouse Model Changes To Human Pdmentioning
confidence: 99%
“…When comparing the DEGs obtained in this study to the list of DEGs from a meta-analysis of transcriptomics data from post-mortem brain samples from the SN midbrain region from a previous study [61], we observed a significant overlap with the DEGs between genotypes (HET versus WT) for 3-month-old mice (45 genes, Fisher's exact test p value = 0.003, see Table S7), but no overlap with the 5 DEGs obtained for 9-month-old mice. Furthermore, also the higher level analyses of molecular pathways and GO terms point to cellular processes that match with previously proposed mechanisms associated with PD (see previous sections).…”
Section: Comparability Of the Mouse Model Changes To Human Pdmentioning
confidence: 99%